Failure analysis of the pulleys during the press-fit assembling process. (April 2015) - Zdravecká, Eva; Ondáč, Miroslav; Tkáčová, Jana; Vojtko, Marek; Slota, Ján
Highlights: A failure of pulleys during the press-fit assembling process has been analyzed. The metallographic examination using light microscopy, SEM/EDX evaluation and chemical analyses were carried out. Cooperative influences of inhomogeneous structure, elongated sulphides and increased carbon content were determined as the cause of the fracture of pulleys material. Abstract: The present article highlights failure investigation of the pulleys during a press-fit assembling process. Pulleys are used to transmit power between rotational mechanical elements. Failure analysis was performed by metallographic evaluation using light microscopy, SEM and EDX, and chemical analyses. It was found that cooperative influence of higher carbon content with combination of elongated sulphides is reason for pulleys cracking. Steel cleanliness and homogeneous structure is an important factor for users of steel. The success of production process is connected with the optimal quality of steel.